The Sources of the Narrative of Siffin Agreement (Journal of the College of Education for Women, 2019)
We can conclude that version A is substantially genuine while version B is spurious. an Attempt has been made above to show relevance of this to our understanding of the agreement itself .The central issue of sunna to which recourse was to be had must of course be connected with development of the meaning of the word sunna from the broader (way of Proceeding ) and (generally agreed practice).Any sweeping judgements about the invalidity of reports transmitted by shiis or supposed shii are out of place. theestablishment of realistic criteria for the appreciation of early sources for Islamic history is subject which is still in Its infancy